MICROPROCESSOR DEVICE FOR ESTIMATING THE LEVEL OF RADIAL RUN OF A HYDROGENERATOR ROTOR BY THERMAL VISION METHOD - GRABKO, VOLODYMYR; GRABKO, VALENTYN; OSCHEPKOV, VICTOR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The paper proposes an approach that involves installing a line of infrared sensors along the radius of the hydrogenerator rotor with signals output from them to a microcontroller. Part of the specified line extends beyond the limits of rotation of the rotor edge. During the rotation of the rotor, at each moment of time, a small fragment of the rotor surface (segment) falls into the field of view of the infrared sensor array. As the rotor rotates, each segment of the surface is scanned, resulting in a thermal portrait of the hydrogenerator rotor surface. When there is no radial runout of the rotor shaft, the infrared sensors extending beyond the rotor edge do not participate in forming the thermal portrait of the hydrogenerator rotor. In the presence of radial rotor runout at the outputs of infrared sensors that extend beyond the edge of the rotor rotation space, depending on the intensity of the runout, signals appear in a number of segments indicating a deviation of the rotor shaft rotation axis from its vertical position. It is obvious that the greater the amplitude of the deviation of the rotor shaft axis from the vertical position and the more signals that exceed the lower fixation threshold appear in the larger number of sensors located in different neighboring segments outside the rotor edge, the more the level of radial runout of the hydrogenerator rotor shaft increases. Signals from infrared sensors are processed by a microprocessor device in accordance with the above operating algorithm. In case of fixing the fact of radial runout, a warning signal is issued to the operating personnel. All information regarding the measurement of the thermal portrait of the hydrogenerator rotor is stored in the database of operational personnel, which allows investigating the process of deterioration of the technical condition of the hydrogenerator. In this way, the level of radial runout of the hydrogenerator rotor is assessed as an alternative approach to known traditional systems for monitoring the level of radial runout of the rotor. A conclusion was made about the feasibility of combining the proposed device with other systems for monitoring the technical condition of hydraulic units